Early screening of lung function by electrical impedance tomography in people with normal spirometry reveals unrecognized pathological features - Shuoyao Qu; Enzhi Feng; Daihan Dong; Lin Yang; Meng Dai; Inéz Frerichs; Shaojie Liu; Yi Gao; Jinping Zheng; Liqiang Song; Zhanqi Zhao (Nature Communications)
Abstract Early detection of lung function impairment is crucial. However, the sensitivity of spirometry in detecting early lung function deterioration is limited. In this study, lungs of 3180 healthy participants scheduled for annual health check were screened. Electrical impedance tomography measurements were conducted in 130 participants with normal spirometry for concept establishment phase and 105 for validation phase. A follow-up CT examination was suggested for participants with abnormal regional time constant or tobacco consumption ≥10 pack-years. Using CT as reference, the sensitivity and specificity of electrical impedance tomography-based screening were 81.3% and 50.0%, respectively in the concept establishment phase. In the validation phase, the sensitivity and specificity were 77.9% and 50.0%. In this study we show that conventional spirometry may not capture early changes that occur at a regional level. The regional time constant based on electrical impedance tomography can be a promising tool for early screening of lung function impairment. Clinical trial registration: ChiCTR2300076673, www.chictr.org.cn .